Content authentication of H.264/AVC video stream based on semi-fragile watermarking - WANG Xiao-jing; YANG Gao-bo; ZHU Ning-bo (Tongxin xuebao)
For the low bit-rate H.264/AVC video stream,a content authentication scheme was proposed by using semi-fragile watermarking.The energy relationship between two groups of DCT blocks in I frame was utilized to generate content based feature code,which was embedded into low-magnitude DCT coefficients by modifying their signs according to their distribution.An error norm function was introduced to keep the bit-rate relatively stable.Moreover,the frame numbers of P frames were embedded into AC coefficients by utilizing the statistical properties of positive and negative signs.Tamper detection was realized by comparing the extracted watermark and reconstructed authentication code.Experimental results demonstrate the effectiveness of the proposed approach.